2016
DOI: 10.3390/ijms17020240
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-222-3p in c-Src-Mediated Regulation of Osteoclastogenesis

Abstract: MicroRNAs (miRNAs) are small non-coding RNAs that play a mostly post-transcriptional regulatory role in gene expression. Using RAW264.7 pre-osteoclast cells and genome-wide expression analysis, we identified a set of miRNAs that are involved in osteoclastogenesis. Based on in silico analysis, we specifically focused on miR-222-3p and evaluated its role in osteoclastogenesis. The results show that the inhibitor of miR-222-3p upregulated the mRNA levels of nuclear factor of activated T-cells, cytoplasmic 1 (NFAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…For this reason we studied treatment-naïve women with osteoporosis who presented with clinical vertebral fractures and we obtained blood at the same time following the fracture as in the denosumab-treated women. We show here that Dmab/Fx+ women had significant decreases in the expression of miRs that negatively regulate the osteoclast formation and activity in vitro (15,16,17) associated with increases in the mRNA of their target genes RANK and GTSK in serum; in addition, had higher levels of bone turnover markers. These findings together imply the upregulation of osteoclastogenesis and osteoclast activity as a critical contributor to the increased vertebral fragility following the discontinuation of denosumab treatment.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…For this reason we studied treatment-naïve women with osteoporosis who presented with clinical vertebral fractures and we obtained blood at the same time following the fracture as in the denosumab-treated women. We show here that Dmab/Fx+ women had significant decreases in the expression of miRs that negatively regulate the osteoclast formation and activity in vitro (15,16,17) associated with increases in the mRNA of their target genes RANK and GTSK in serum; in addition, had higher levels of bone turnover markers. These findings together imply the upregulation of osteoclastogenesis and osteoclast activity as a critical contributor to the increased vertebral fragility following the discontinuation of denosumab treatment.…”
Section: Discussionmentioning
confidence: 70%
“…For example, Seeliger et al (13) showed a robust association between the expression of certain miRs in serum and bone tissue in patients with osteoporosis and fractures and Weilner et al reported that miRs in serum of patients with fractures can influence osteogenic differentiation (14). We analyzed in the serum of our patients the expression of 3 miRs (miR-21, miR-503 and miR-222-2) and of mRNAs of their related genes that are involved in osteoclast formation and function (RANKL, RANK, cathepsin K (CTSK) and tartrate-resistant acid phosphatase (TRAP)) respectively (15,16,17).…”
Section: Serum Microrna and Gene Analysesmentioning
confidence: 98%
“…lncRNA-MAYA is involved in the regulation of DC-STAMP indirectly as it mediates the activation of yes-associated protein 1 (YAP1), which upregulates CTGF expression, leading to elevated cancer cell-induced osteoclastogenesis and bone resorption [ 136 ]. miR-222-3p is also reported to modulate the expression of DC-STAMP [ 137 ].…”
Section: Involvement Of Ncrnas In Osteoclast Differentiationmentioning
confidence: 99%
“…Downregulated miR-9 and miR-181a promote Cbl expression and activity by targeting Cbl, which is also a potential target of miR-422a [ 47 , 153 ]. Downregulation of miR-222-3p supports osteoclast adhesion and migration by targeting c-Src, while pit formation activity of multinucleated osteoclasts is decreased by miR-222-3p gain-of-function [ 137 ]. CREB-binding protein (CBP, also known as phosphoprotein membrane anchor with glycosphingolipid microdomains 1 (PAG1)), which is also a potential target of miR-422a, inhibits c-Src activity in a dose-dependent manner.…”
Section: Involvement Of Ncrnas In Osteoclast Differentiationmentioning
confidence: 99%
“…BMP2 induces osteogenic differentiation via the hsa_circ_0019142/ hsa_circ_0005846 target miRNA-mRNA regulation network (47), in which the level of ALP, SP7, and RUNX2 mRNA expression increases significantly. Moreover, hsa_circ_0019142 interacts with miR-222-3p and miR-7067-5p (48), with the former functioning as an osteoclast inhibitor (49).…”
Section: Circrna In Osteoblasts and Osteoclastsmentioning
confidence: 99%